Variability of space-use patterns in a free living eusocial rodent, Ansell's mole-rat indicates age-based rather than caste polyethism - Šklíba, Jan; Lövy, Matěj; Burda, Hynek; Šumbera, Radim (Scientific reports, 2016)
Eusocial species of African mole-rats live in groups cooperating on multiple tasks and employing division of labour. In captivity, individuals of the same group differ in cooperative contribution as well as in preference for a particular task. Both can be viewed as polyethism. However, little information is available from free-ranging mole-rats, which live in large burrow systems. We made an attempt to detect polyethism in the free-living Ansell's mole-rat (Fukomys anselli) as differences in individuals' space-use patterns. We radio-tracked 17 adults from five groups. Large individuals, including breeding males, spent more time inside the nest than smaller individuals. Breeding females were more often located <10 m from the nest in comparison to non-breeding females, who were relatively more often located 30-90 m and exclusively >90 m from the nest. One non-breeding female even conducted a brief intrusion into a neighbouring group's territory via an open tunnel connection. A significant part of the variability in mole-rat space-use patterns was explained by body mass which is probably related to age in this species. This result can therefore be attributed to age polyethism. There was no apparent discontinuity in the space-use patterns of non-breeders that would indicate existence of castes.
Keywords: Sex Factors; Reproduction; rozmnožování; kooperační chování; prostorové chování; Female; věkové faktory; zvířata; Zambie; sexuální faktory; ženské pohlaví; Male; mikroftalmičtí podzemní hlodavci; Mole Rats; Zambia; Animals; Age Factors; Spatial Behavior; mužské pohlaví; Cooperative Behavior